Resolving the Ambiguous Expectations of Academic Integrity - Bens, Susan (Canadian Perspectives on Academic Integrity, 2021)
Students encounter wide-ranging teaching and learning contexts and approaches in Canadian post secondary institutions. As a result, they receive and perceive mixed messages when it comes to academic integrity. The purpose of this session is to remind us, as educators/ scholars/researchers what it is like to be the “novice” in our disciplines and fields. The presenter calls for more explicit and contextual teaching of the norms and skills required for academic integrity. This will lead to discussion of (1) what should be done at the program level to explain and educate students on ethical academic and professional practices; and (2) the value and the limits of awareness campaigns and standardized syllabus statements. The session foreshadows a chapter in a forthcoming edited book about academic integrity in Canada and fits with “best practices and emerging ideas in academic integrity policy development.”